Induction of Ploidy Level on Three Patchouli (Pogostemon cablin Benth) Cultivars by Colchicine In Vitro - Amien, Suseno; Darmawan, Nikkita Putri; Fathya, Daniya (Universitas Padjadjaran, 2023)
Patchouli plants produce essential oils and are used as a raw material and fixative agent for perfumes. The most widely cultivated patchouli plant in Indonesia is Aceh patchouli. Sexual propagation in Aceh patchouli plants is impossible as it does not flower. Genetic diversity can be elevated through another method, such as polyploidy induction using colchicine. This research aimed to evaluate the state-of-the-art application of polyploidization techniques as a breeding tool for callus-based explants. A completely randomized design with a factorial pattern was used in this experiment consisting of two factors, patchouli cultivars (Sidikalang, Tapak Tuan, and Lhokseumawe) and colchicine concentration (0.0%, 0.2%, 0.5%, 0.7%, and 1%). The result showed an interaction between three patchouli cultivars with colchicine concentration on callus size and color characters. In Sidikalang cultivar, 0.2% colchicine concentration affects the character of callus emergence time and has more buds. In cultivar Tapak Tuan, the application of colchicine 0.2% affects the callus size character and has the highest number of buds. In the Lhokseumawe cultivar, giving 0.5% colchicine affects the character of callus appearance time, callus size, and callus color. Concentrations of 0.2% and 1.0% colchicine in Sidikalang and Tapak Tuan calluses increased the number of chromosomes, ranging from 2n (32), 3n (48), and 4n (64). The implication of the research could be disclosure of an opportunity to create a new superior variety.